The Investigation of the Untapped Winemaking Potential of the Grape Variety “Hastakot” - Gabrielyan, A. H.; Iskandaryan, G. B. (ՀԱԱՀ հիմնադրամ)
Research works demonstrate a rising demand for high-quality wine in Armenia. Our objective was to produce premium red and rosé wines using the relatively unexplored grape variety “Hastakot”. Throughout the research, we utilized various winemaking technologies to produce red and rosé wines of the grape variety “Hastakot”. Simultaneously, multiple physicochemical and sensory attributes were investigated in the produced must and wine. The obtained results highlight the ability to make unique wines from the grape variety “Hastakot”, indicating a potential market impact and gaining consumer appreciation.
Keywords: Food Science and Technology